Characteristics And Effects Of Acute Bronchiolitis In Infectious Children (Citomegalovirus) (Eurasian Medical Research Periodical, 2023)
The article is dedicated to the problem of acute bronchitis in children. The relevance of this problem is obvious: according to conservative estimates, more than 150 million cases of bronchiolitis are registered annually.7-13% of these cases require hospital treatment and 1-3%-hospitalization in an ICU. The most common etiologic factor is the virus-respiratory synsytial (the vast majority of cases-60- 80%)cytomegalovirus, influenza viruses, parainfluenza, adenovirus, coronavirus are also important agents. A number of factors can cause the evolution of bronchiolitis in 0- 2 years-old children. Premature infants, children with bronchopulmonarydysplasia, bottle-fed children, and patients with congenital malformations and immunodeficiencies undergo bronchiolitis especially hard